S100A8-CAMKK2-AMPK axis confers the protective effects of mild hypothermia against cerebral ischemia-reperfusion injury in rats - Dandan Zhang; Yuting Dai; Xiaoyan Xu; Fuguo Ma; Mingshan Wang; Weiwei Qin (Scientific Reports)
Abstract To investigate the neuroprotective mechanism of mild hypothermia (MH) in ameliorating cerebral ischemia reperfusion (IR) injury. The Pulsinelli’s four-vessel ligation method was utilized to establish a rat model of global cerebral IR injury. To investigate the role of S100A8 in MH treatment of cerebral IR injury, hippocampus-specific S100A8 loss or gain of function was achieved using an adeno-associated virus system. We examined the effect of S100A8 over-expression or knock-down on the function of the SH-SY5Y cell line subjected to oxygen-glucose deprivation reoxygenation (OGDR) injury under MH treatment and delved into the underlying mechanisms. MH significantly ameliorates IR-induced neurological injury in the brain. Similarly to MH, knock-down of S100A8 significantly reduced neuronal oxidative stress, attenuated mitochondrial damage, inhibited apoptosis, and improved cognitive function in IR rats. Conversely, over-expression of S100A8 attenuated MH’s protective effect and aggravated brain IR injury. In vitro, low expression of S100A8 significantly inhibited the decline in mitochondrial membrane potential induced by OGDR, reduced oxidative stress response, and decreased cell apoptosis, acting as a protective agent nearly equivalent to MH in SH-SY5Y cells. However, over-expression of S100A8 significantly inhibited these protective effects of MH. Mechanistically, MH down-regulated S100A8 expression, enhancing mitochondrial function via activation of the CAMKK2/AMPK signaling pathway. Moreover, with MH treatment, the administration of CAMKK2 and AMPK inhibitors STO-609 and Dorsomorphin significantly increased oxidative stress, mitochondrial damage, and cell apoptosis, thereby diminishing MH’s neuroprotective effect against cerebral IR injury. Our study identified S100A8 as a master regulator that enables MH to ameliorate neurological injury during the early stage of cerebral IR injury by enhancing mitochondrial function. By targeting the S100A8-initiated CAMKK2/AMPK signaling pathway, we may unlock a novel therapeutic intervention or develop a refined MH therapeutic strategy against cerebral IR injury.